Surface-treated glass cloth, prepreg, and printed wiring board

By using the first silane coupling agent and the second silane coupling agent of methacryloyl group in the glass cloth surface treatment layer, the wrinkle problem of glass cloth in the prior art during the production of prepreg and in the printed wiring board is solved. The problem of insufficient insulation reliability achieves the effect of high insulation reliability and hardening of the hand.

CN119145219APending Publication Date: 2024-12-17NITTO BOSEKI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411282320.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2020-08-25
Filing Date
2021-07-07
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing surface-treated glass cloth is prone to wrinkles when manufacturing prepregs, and it is difficult to obtain high insulation reliability when used in printed wiring boards, especially difficult to handle glass cloth with soft feel.

Method used

The first silane coupling agent and the second silane coupling agent containing at least one methacryloyl group are used to adopt the surface treatment layer. The second silane coupling agent has a fast hydrolysis speed and high reactivity, so that the feel of the glass cloth can be hardened. And the reaction with the resin is not hindered, thereby achieving high insulation reliability in the printed wiring board.

Benefits of technology

High insulation reliability is achieved in printed wiring boards, while avoiding wrinkles during prepreg manufacturing, and making the feel of the glass cloth harden.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005042037450000131
    Figure BDA0005042037450000131
  • Figure BDA0005042037450000141
    Figure BDA0005042037450000141
Patent Text Reader

Abstract

The invention provides a surface-treated glass cloth, a prepreg, and a printed wiring board. High insulation reliability can be obtained on the printed wiring board, and wrinkles are not easily generated when the prepreg is manufactured. The surface-treated glass cloth is provided with a surface-treated layer on the surface, and the surface-treated layer contains a first silane coupling agent having at least one methacryloyl group and a second silane coupling agent represented by general formula (1): X (R) 3-nS iYn... (1). (In the formula, X is an alkyl group having 1-4 carbon atoms, R represents one group independently selected from the group consisting of a methyl group, an ethyl group and a phenyl group, Y represents an alkoxy group having 1-6 carbon atoms independently, and n is an integer of 1-3.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an invention patent application with an application date of July 7, 2021, an application number of 202180034321.1 (international application number PCT / JP2021 / 025697), and an invention name of "Surface-treated glass cloth, prepreg and printed wiring board". Technical Field

[0002] The present invention relates to a surface treated glass cloth, a prepreg and a printed wiring board. Background Art

[0003] Conventionally, as a glass cloth used in a printed wiring board, there is known a glass cloth having a surface treatment layer, the surface of which has a silane coupling agent having at least one methacryl group such as 3-methacryloxypropyltrimethoxysilane (γ-methacryloxypropyltrimethoxysilane) on its surface (for example, refer to Patent Document 1).

[0004] According to the surface treated glass cloth described in Patent Document 1, the whitening distance indicating the degree of interface separation between glass and resin on the surface treated layer when formed into a printed wiring board is small, and the printed wiring board can obtain high insulation reliability.

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent No. 6734422 Summary of the invention

[0008] Problems to be solved by the invention

[0009] However, the surface treated glass cloth described in the above patent document 1 has the disadvantages of being soft to the touch and being prone to wrinkles when manufacturing prepreg. In addition, in recent years, glass cloth used in printed wiring boards has also been required to be thinner due to the miniaturization and thinning of electronic devices, and wrinkles are easily generated when manufacturing thinner glass cloths, so it is particularly difficult to handle surface treated glass cloths that are soft to the touch.

[0010] The object of the present invention is to provide a surface-treated glass cloth that can obtain high insulation reliability in a printed wiring board and is less likely to wrinkle when manufacturing a prepreg, a prepreg using the surface-treated glass cloth, and a printed wiring board using the surface-treated glass cloth in order to solve the above-mentioned disadvantages.

[0011] Means for solving problems

[0012] To achieve the above object, the surface treated glass cloth of the present invention comprises a surface treated layer on its surface, wherein the surface treated layer comprises a first silane coupling agent having at least one methacryloyl group and a second silane coupling agent represented by the following general formula (1).

[0013] X(R) 3-n S Y n …(1)

[0014] (In the formula, X is an alkyl group having 1 to 4 carbon atoms, R represents one group independently selected from the group consisting of a methyl group, an ethyl group and a phenyl group, Y represents an alkoxy group having 1 to 6 carbon atoms, and n is an integer of 1 to 3.)

[0015] The surface treated glass cloth of the present invention has a surface treated layer containing the first silane coupling agent and the second silane coupling agent on its surface, thereby achieving high insulation reliability in a printed wiring board and having a hard texture, so wrinkles are less likely to occur during the production of prepreg.

[0016] The second silane coupling agent has a fast hydrolysis rate and high reactivity of silanol, so the adsorption of the second silane coupling agent to the glass cloth is increased, and the hand feel of the glass cloth can be hardened. In addition, the second silane coupling agent has a short alkyl chain and a small molecular weight, and does not hinder the reaction of the first silane coupling agent with the resin, so high insulation reliability can be obtained in the printed wiring board.

[0017] In the surface-treated glass cloth of the present invention, preferably, X in the general formula (1) of the second silane coupling agent is a methyl group or an ethyl group, and more preferably a methyl group.

[0018] In addition, in the surface-treated glass cloth of the present invention, preferably, the total content of the first silane coupling agent and the second silane coupling agent is in the range of 0.03 to 1.50 mass % of the total mass of the surface-treated glass cloth, and the ratio of the content of the second silane coupling agent to the content of the first silane coupling agent (the content of the second silane coupling agent / the content of the first silane coupling agent) is in the range of 0.01 to 0.25, and more preferably, the ratio of the content of the second silane coupling agent to the content of the first silane coupling agent is in the range of 0.03 to 0.17.

[0019] The total content of the first silane coupling agent and the second silane coupling agent in the surface-treated glass cloth of the present invention is in the range of 0.03 to 1.50 mass % of the total mass of the surface-treated glass cloth, and the ratio of the content of the second silane coupling agent to the content of the first silane coupling agent (content of the second silane coupling agent / content of the first silane coupling agent) is in the range of 0.01 to 0.25, thereby achieving a balanced effect of high insulation reliability in a printed wiring board and hardening the feel of the glass cloth.

[0020] In the surface-treated glass cloth of the present invention, when the total content of the first silane coupling agent and the second silane coupling agent is less than 0.03% by mass of the total mass of the surface-treated glass cloth, the amount of silane coupling agent attached is small, so the interface adhesion with the resin is deteriorated, and high insulation reliability cannot be obtained. In addition, when the total content of the first silane coupling agent and the second silane coupling agent exceeds 1.05% by mass of the total mass of the surface-treated glass cloth, the concentration of the silane coupling agent in the glass treatment agent aqueous solution needs to be increased, and the stability of the glass treatment agent aqueous solution is deteriorated, so it is difficult to perform long-term stable and continuous production.

[0021] In addition, in the surface-treated glass cloth of the present invention, when the ratio of the content of the second silane coupling agent to the content of the first silane coupling agent (content of the second silane coupling agent / content of the first silane coupling agent) is less than 0.01, the effect of hardening the hand feel cannot be obtained, and when the above ratio exceeds 0.25, dehydration condensation of the second silane coupling agent is likely to occur, resulting in difficulty in long-term stable and continuous production.

[0022] In the surface treated glass cloth of the present invention, it is preferred that the surface treated layer does not contain a surfactant. In the surface treated glass cloth of the present invention, the surface treated layer does not contain a surfactant, so that the impregnation property is improved and high insulation reliability can be obtained in a printed wiring board.

[0023] In addition, the thickness of the surface-treated glass cloth of the present invention is preferably in the range of 5 to 25 μm. The surface-treated glass cloth of the present invention can also obtain the effects of the present invention when the thickness exceeds 25 μm, but by setting the thickness in the range of 5 to 25 μm, the high insulation reliability of the printed wiring board and the effect of hardening the feel of the glass cloth can be obtained in a balanced manner. In addition, it is technically difficult to manufacture the surface-treated glass cloth of the present invention with a thickness of less than 5 μm.

[0024] Furthermore, the prepreg of the present invention is characterized by comprising the surface-treated glass cloth of the present invention, and the printed wiring board of the present invention is characterized by comprising the surface-treated glass cloth of the present invention. DETAILED DESCRIPTION

[0025] Next, embodiments of the present invention will be described in further detail.

[0026] The surface-treated glass cloth of the present embodiment includes a surface-treated layer on the surface, and the surface-treated layer contains a first silane coupling agent having at least one methacryloyl group and a second silane coupling agent represented by the following general formula (1).

[0027] X(R) 3-n S Y n …(1)

[0028] (In the formula, X is an alkyl group having 1 to 4 carbon atoms, R represents one group independently selected from the group consisting of a methyl group, an ethyl group and a phenyl group, Y represents an alkoxy group having 1 to 6 carbon atoms, and n is an integer of 1 to 3.)

[0029] In the surface-treated glass cloth of the present embodiment, in the general formula (1), X of the second silane coupling agent is preferably a methyl group or an ethyl group, and more preferably a methyl group.

[0030] The surface-treated glass cloth according to the present embodiment can be produced, for example, as follows.

[0031] First, a predetermined glass batch material (glass raw material) is melted and fiberized to obtain glass filaments. The glass composition of the glass filaments is not particularly limited, but is preferably a composition of E glass, T glass, NE glass, L glass, etc. From the viewpoint of low dielectric constant and low dielectric loss tangent, the glass composition of the glass filaments is more preferably NE glass or L glass. Specifically, it is more preferred to adopt the following composition: relative to the total amount, it contains: SiO2 in the range of 48.0 to 62.0 mass %; B2O3 in the range of 17.0 to 26.0 mass %; Al2O3 in the range of 9.0 to 18.0 mass %; MgO in the range of 0 to 6.0 mass %; CaO in the range of 0.1 to 9.0 mass %; Na2O, K2O and Li2O in the range of 0 to 0.5 mass % in total; TiO2 in the range of 0 to 5.0 mass %; SrO in the range of 0 to 6.0 mass %; P2O5 in the range of 0 to 6.0 mass %; F2 and Cl2 in the range of 0 to 3.0 mass %.

[0032] Here, regarding the measurement of the content of each component of the above-mentioned glass composition, Li as a light element can be measured using an ICP emission spectrometer, and other elements can be measured using a wavelength dispersive fluorescent X-ray analyzer.

[0033] The following method can be used as a measurement method. After cutting the glass cloth (when organic matter is attached to the surface of the glass cloth, or when the glass cloth is mainly contained in the organic matter (resin) as a reinforcing material, for example, the organic matter is removed by heating in a muffle furnace at 300 to 600°C for about 2 to 24 hours) into appropriate sizes, it is placed in a platinum crucible, kept at a temperature of 1550°C in an electric furnace for 6 hours, and melted while stirring, thereby obtaining a homogeneous molten glass. Then, after the obtained molten glass is poured onto a carbon plate to make glass scraps, it is crushed and powdered. After the glass powder is heated and decomposed with acid, Li as a light element is quantitatively analyzed using an ICP emission spectrophotometer. After the glass powder is formed into a disc shape with a press, other elements are quantitatively analyzed using a wavelength dispersive fluorescent X-ray analyzer. After these quantitative analysis results are converted into oxides, the content and total amount of each component are calculated, and the content (mass %) of the above-mentioned components can be calculated based on these numerical values.

[0034] The filament diameter of the glass filament is not particularly limited, but in the application of a printed wiring board, the filament diameter is preferably 10 μm or less, more preferably 8 μm or less, and particularly preferably in the range of 3 to 5 μm.

[0035] The glass filaments are, for example, bundled into glass fiber yarns in a number ranging from 25 to 500, and preferably 40 to 300, by a known method. Spinning is a method in which a glass batch is melted and fiberized to obtain glass filaments, and then a plurality of the glass filaments are bundled into glass fiber yarns.

[0036] The filament diameter of the glass filaments is the average value of the following measured values: the diameter of the glass filaments constituting the warp or weft is measured using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, trade name: S-3400N, magnification: 3000 times) at 50 cross sections of the warp or 50 cross sections of the weft of the glass cloth. In addition, the number of glass filaments is the average value of the following measured values: the number of glass filaments constituting the warp or weft is measured using a scanning electron microscope (manufactured by Hitachi High-Technologies Corporation, trade name: S-3400N, magnification: 500 times) at 50 cross sections of the warp or 50 cross sections of the glass cloth.

[0037] The glass fiber yarn preferably has a count of 0.8 to 135 tex, more preferably 1 to 25 tex. The glass fiber yarn count (tex) corresponds to the mass (unit: g) of glass fiber per 1000 m.

[0038] Next, the glass fiber is used as a warp or a weft to weave a glass cloth. The weaving method is not particularly limited, and examples thereof include plain weave, satin weave, and twill weave, and the plain weave is preferably used. The fabric density of the glass fiber yarn during the weaving is not particularly limited, and for example, it is preferably in the range of 10 to 150 strands / 25 mm, and more preferably in the range of 40 to 100 strands / 25 mm.

[0039] The fabric density of the glass fiber yarn can be obtained as follows: according to JIS R3420, the number of warp yarns or weft yarns within a range of 25 mm in the warp direction or the weft direction is counted using a fabric analyzer.

[0040] During the weaving, a sizing agent is used in bundling the glass filaments, warping the warp yarns, etc. Examples of the sizing agent include a sizing agent whose coating forming agent component is a starch-based or PVA (polyvinyl alcohol)-based sizing agent. The sizing agent may contain an oil or a softener.

[0041] The amount of the sizing agent in the glass cloth is preferably 0.1 to 3 parts by mass, more preferably 0.5 to 1.5 parts by mass, relative to 100 parts by mass of the glass fiber yarn. It should be noted that the range of the amount of the sizing agent and the amount of the sizing agent when not specifically specified represent the average amount of the sizing agent attached to the warp or weft.

[0042] From the viewpoint of use as a substrate for a printed wiring board, the mass per unit area of ​​the glass cloth obtained by the weaving is preferably 110 g / m 2 On the other hand, from the viewpoint of weavability, the mass per unit area of ​​the glass cloth is preferably 8 g / m 2 above.

[0043] The mass of the glass cloth is the average value of the following values: the mass of three glass cloths cut into a size of 200 mm×200 mm was measured using a scale in accordance with JISR 3420, and the values ​​were converted into the mass per square meter (1 m 2 )’s quality.

[0044] Next, the glass cloth is subjected to a fiber-opening treatment. Examples of the fiber-opening treatment include: fiber-opening using water flow pressure; fiber-opening using high-frequency vibration using a liquid as a medium; fiber-opening using the pressure of a fluid having a surface pressure; fiber-opening using roller pressure, etc. In the fiber-opening treatments described above, when fiber-opening using water flow pressure or fiber-opening using high-frequency vibration using a liquid as a medium is adopted, it is possible to reduce the deviation of the yarn width after the fiber-opening treatment of the warp and weft yarns, and therefore these two fiber-opening treatments are preferred. In addition, a plurality of fiber-opening treatment methods may be used in combination in the fiber-opening treatments described above.

[0045] Next, the glass cloth subjected to the fiber opening treatment is subjected to a deoiling treatment. The deoiling treatment can be performed, for example, by placing the glass cloth in a heating furnace at an ambient temperature in the range of 350°C to 450°C for a period of 40 to 80 hours to heat and decompose the spinning sizing agent and weaving sizing agent attached to the glass cloth.

[0046] Next, the glass cloth subjected to the above-mentioned deoiling treatment is immersed in an aqueous solution of a surface treatment agent, and after removing excess water, it is heated and dried at a temperature range of 80 to 180° C., for example, at 110° C., for a time range of 1 to 30 minutes, for example, for 5 minutes, thereby obtaining the surface-treated glass cloth of the present embodiment.

[0047] As the surface treatment agent aqueous solution, the following aqueous solution can be used: the first silane coupling agent having at least one methacryloyl group and the second silane coupling agent represented by the following general formula (1) are contained in an amount of 0.1 to 2.0% by weight, based on the total amount of the surface treatment agent aqueous solution, and the second silane coupling agent is contained in an amount of 0.5 to 2.0% by weight, based on the solid content, of a weak acid (e.g., acetic acid, citric acid, propionic acid, etc.) as a pH adjuster.

[0048] X(R) 3-n S Y n …(1)

[0049] (In the formula, X is an alkyl group having 1 to 4 carbon atoms, R represents one group independently selected from the group consisting of a methyl group, an ethyl group and a phenyl group, Y represents an alkoxy group having 1 to 6 carbon atoms, and n is an integer of 1 to 3.)

[0050] Examples of the silane coupling agent having at least one methacryl group include 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropylmethyldiethoxysilane, and 3-methacryloxypropyltriethoxysilane.

[0051] In addition, examples of the second silane coupling agent represented by the general formula (1) include methyltrimethoxysilane, methyltriethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, trimethylethoxysilane, ethyltrimethoxysilane, ethyltriethoxysilane, propyltrimethoxysilane, propyltriethoxysilane, and butyltrimethoxysilane. The second silane coupling agent preferably has X in the general formula (1) as a methyl group or an ethyl group, and examples of such a second silane coupling agent include methyltrimethoxysilane, methyltriethoxysilane, ethyltrimethoxysilane, and ethyltriethoxysilane. The second silane coupling agent more preferably has X in the general formula (1) as a methyl group, and examples of such a second silane coupling agent include methyltrimethoxysilane and methyltriethoxysilane, and methyltrimethoxysilane is most preferred.

[0052] In the surface-treated glass cloth of the present embodiment, the total content of the first silane coupling agent and the second silane coupling agent is preferably in the range of 0.03 to 1.50 mass % relative to the total amount of the surface-treated glass cloth, more preferably in the range of 0.05 to 1.20 mass %, further preferably in the range of 0.1 to 1.0 mass %, particularly preferably in the range of 0.2 to 0.8 mass %, particularly preferably in the range of 0.3 to 0.7 mass %, and most preferably in the range of 0.4 to 0.6 mass %.

[0053] In addition, in the surface-treated glass cloth of the present embodiment, the ratio of the content of the second silane coupling agent to the content of the first silane coupling agent (content of the second silane coupling agent / content of the first silane coupling agent) is preferably in the range of 0.01 to 0.25, more preferably in the range of 0.03 to 0.20, further preferably in the range of 0.03 to 0.17, and most preferably in the range of 0.10 to 0.17.

[0054] As a result, the surface treated glass cloth of the present embodiment having a surface treated layer containing the first silane coupling agent having at least one methacryloyl group and the second silane coupling agent represented by the above general formula (1) can be obtained.

[0055] In the surface treated glass cloth of the present embodiment, the surface treated layer preferably does not contain a surfactant and has a thickness of preferably 5 to 60 μm, more preferably 5 to 40 μm, and further preferably 5 to 25 μm.

[0056] Here, as the thickness of the surface-treated glass cloth, an average value of the thicknesses measured at 15 locations on the surface-treated glass cloth using a micrometer in accordance with JIS R3420 can be adopted.

[0057] Next, examples, comparative examples, and reference examples of the present invention are described.

[0058] (Example 1)

[0059] In this embodiment, the gauze specification #1017 under the IPC 4412 standard is woven (glass composition: NE glass, yarn used: BC3000 (filament diameter 4.0 μm, yarn weight 1.5 tex), warp yarn fabric density: 95 yarns / 25 mm, weft yarn fabric density: 95 yarns / 25 mm, mass per unit area: 11.4 g / m 2 ) is subjected to fiber opening by spraying a high-pressure water flow of 40°C with a pressure of 2 MPa onto the glass cloth, and is subjected to deoiling treatment by heating at a temperature of 400-450°C for 60 hours. Then, the deoiled glass cloth is immersed in an aqueous solution of a glass treatment agent to remove excess water, and is heated and dried at a temperature of 110°C for 5 minutes to obtain the surface-treated glass cloth of this embodiment.

[0060] The glass treatment agent aqueous solution was prepared by using 1.0 mass % of 3-methacryloxypropyltrimethoxysilane (manufactured by Dow Toray Co., Ltd.) as a first silane coupling agent and 0.15 mass % of methyltrimethoxysilane (manufactured by Momentive Performance Materials Japan LLC) as a second silane coupling agent, mixing acetic acid with water to give 0.5 mass %, and stirring with a magnetic stirrer for 1 hour.

[0061] The obtained surface-treated glass cloth was cut into 350 mm×400 mm, and the obtained surface-treated glass cloth piece was immersed in a polyphenylene ether resin varnish, and pre-dried at a temperature of 150° C. for 10 minutes to obtain a prepreg. The polyphenylene ether resin varnish is composed of 450 parts by mass of oligophenylene ether (manufactured by Mitsubishi Gas Chemical Co., Ltd., trade name: OPE-2St), 100 parts by mass of triallyl isocyanurate (manufactured by Evonik Japan Co., Ltd., trade name: TAI CROS), 4 parts by mass of α,α'-di(tert-butylperoxy)diisopropylbenzene (manufactured by NOF Corporation, trade name: Perbuty l P), and 250 parts by mass of toluene (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.).

[0062] Next, four of the above prepregs were stacked, and the fiber films were stacked one above the other, and heated and pressed for a predetermined time using a vacuum hot press (produced by Kitagawa Seiki Co., Ltd.) to obtain a laminated plate having a thickness of about 0.2 mm.

[0063] Next, the laminated board prepared in this embodiment was cut into 7cm×4cm, and a diamond tool was used to cut 2cm long slits in the vertical and horizontal directions to prepare a test piece. A 1 mol / L NaOH (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) aqueous solution was added to a beaker and heated to a temperature of 60°C. After the test piece was immersed in the aqueous solution for 24 hours, a digital microscope (manufactured by KEYENCE Co., Ltd.) was used to measure the whitening distance of the interface peeling between the resin and the glass in the warp direction and the weft direction at a magnification of 100 times. In the measurement, 24 locations in the warp direction and the weft direction were measured respectively, and the average value was calculated and used as the whitening distance. The whitening distance caused by the peeling is correlated with the insulation reliability of the printed wiring board. The shorter the whitening distance, the higher the insulation reliability.

[0064] Next, cut the surface treated glass cloth obtained in this embodiment into 90mm×30mm pieces as glass cloth pieces for measuring the feel. The feel is measured according to the rigid-flexibility test based on the sliding method of JISL 1096. Fix one end of the short side of the glass cloth piece for measuring the feel to a horizontal platform with a length of 30mm in the long side direction, set the other part as a free end, and place it on a moving table whose upper surface is consistent with the horizontal platform. Lower the moving table based on the upper surface of the horizontal platform, and measure the moving distance of the top center of the free end away from the moving table. Use 5 glass cloth pieces for measuring the feel to measure the moving distance, and calculate the average value. There is a correlation between the moving distance of the moving table and the feel of the glass cloth. The shorter the moving distance, the harder the feel of the glass cloth.

[0065] Next, the surface treated glass cloth obtained in this embodiment was cut into 60 mm × 40 mm to prepare an impregnation evaluation test piece. The impregnation evaluation test piece was immersed in benzyl alcohol, and the time from just after immersion to when the benzyl alcohol completely penetrated into the glass cloth piece for impregnation evaluation was measured in the weft direction. Five glass cloth pieces for impregnation evaluation were used for measurement, and the average value was calculated. The measurement results of whitening distance, feel, and impregnation are shown in Table 1. It should be noted that in Table 1, 3-methacryloxypropyltrimethoxysilane is abbreviated as "methacrylic silane" and methyltrimethoxysilane is abbreviated as "methylsilane".

[0066] (Example 2)

[0067] In this embodiment, except that the amount of methyltrimethoxysilane (manufactured by Momentive Performance Materials Japan LLC) as the second silane coupling agent contained in the glass treatment agent aqueous solution is set to 0.05 mass %, the surface-treated glass cloth, prepreg and laminate are prepared in exactly the same manner as in Example 1.

[0068] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this example were used.

[0069] (Example 3)

[0070] In this example, a surface-treated glass cloth, a prepreg, and a laminate were obtained in exactly the same manner as in Example 2, except that 0.001 mass % of polyoxyethylene alkyl ether (manufactured by Toho Chemical Industry Co., Ltd.) as a surfactant was added to the glass treatment agent aqueous solution.

[0071] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this example were used.

[0072] (Example 4)

[0073] In this embodiment, except that the amount of methyltrimethoxysilane (manufactured by Momentive Performance Materials Japan LLC) as the second silane coupling agent contained in the glass treatment agent aqueous solution is set to 0.19 mass %, the surface-treated glass cloth, prepreg and laminate are prepared in exactly the same manner as in Example 1.

[0074] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this Example were used.

[0075] (Example 5)

[0076] In this example, a surface-treated glass cloth, a prepreg, and a laminate were prepared in exactly the same manner as in Example 1, except that 0.05 mass % of propyltrimethoxysilane (manufactured by Shin-Etsu Silicone Co., Ltd.) was used instead of methyltrimethoxysilane (manufactured by Momentive Performance Materials Japan LLC) as the second silane coupling agent contained in the aqueous solution of the glass treatment agent.

[0077] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this example were used.

[0078] In addition, in Table 1, propyltrimethoxysilane is abbreviated as "propylsilane".

[0079] (Example 6)

[0080] In this embodiment, in addition to using the gauze specification #1078 under the IPC 4412 standard (glass composition: NE glass, yarn used: D450 (filament diameter 5.0 μm, yarn weight 10.0 tex), warp yarn fabric density: 53 yarns / 25 mm, weft yarn fabric density: 53 yarns / 25 mm, mass per unit area: 44.0 g / m 2 ) glass cloth, the surface treated glass cloth, prepreg and laminate were prepared in exactly the same manner as in Example 1.

[0081] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this example were used.

[0082] (Comparative Example 1)

[0083] In this comparative example, except that 0.05 mass % of hexyltrimethoxysilane (manufactured by Dow Toray Co., Ltd.) was used instead of methyltrimethoxysilane (manufactured by Momentive Performance Materials Japan LLC) as the second silane coupling agent contained in the glass treatment agent aqueous solution, the surface-treated glass cloth, prepreg and laminate were prepared in exactly the same manner as in Example 1.

[0084] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this comparative example were used.

[0085] In addition, in Table 2, hexyltrimethoxysilane is abbreviated as "hexylsilane".

[0086] (Reference Example 1)

[0087] In this reference example, a surface-treated glass cloth, a prepreg, and a laminate were prepared in exactly the same manner as in Example 1, except that the silane coupling agent contained in the glass treatment agent aqueous solution was 3-methacryloxypropyltrimethoxysilane (manufactured by Dow Toray Co., Ltd.) as the first silane coupling agent in an amount of only 1.0 mass % and the second silane coupling agent was not contained at all.

[0088] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this Reference Example were used.

[0089] (Reference Example 2)

[0090] In this reference example, a surface-treated glass cloth, a prepreg, and a laminate were prepared in exactly the same manner as in Example 6, except that only 1.0 mass % of 3-methacryloxypropyltrimethoxysilane (manufactured by Dow Toray Co., Ltd.) as the first silane coupling agent was contained in the glass treatment agent aqueous solution and no second silane coupling agent was contained.

[0091] Next, the whitening distance, the texture, and the impregnation were measured in exactly the same manner as in Example 1 except that the surface-treated glass cloth and the laminated plate prepared in this Reference Example were used.

[0092] (Table 1)

[0093]

[0094] (Table 2)

[0095]

[0096] It should be noted that the “whitening distance degradation rate” of Examples 1 to 5 and Comparative Example 1 in Tables 1 and 2 represents the rate of increase of the whitening distance relative to the whitening distance of Reference Example 1; the “whitening distance degradation rate” of Example 6 represents the rate of increase of the whitening distance relative to the whitening distance of Reference Example 2. The “hand feel improvement rate” of Examples 1 to 5 and Comparative Example 1 in Tables 1 and 2 represents the rate of decrease of the hand feel relative to the hand feel of Reference Example 1; the “hand feel improvement rate” of Example 6 represents the rate of decrease of the hand feel relative to the hand feel of Reference Example 2.

[0097] In addition, the "feel improvement rate / whitening distance degradation rate" in Tables 1 and 2 is an index showing the degree of insulation reliability in the printed wiring board and the susceptibility of wrinkles to be generated when manufacturing the prepreg. The larger the value, the higher the insulation reliability in the printed wiring board and the less likely wrinkles to be generated when manufacturing the prepreg.

[0098] It is obvious from Table 1 and Table 2 that the surface treated glass cloths of Examples 1 to 6 have a larger value of the hand feel improvement rate / whitening distance degradation rate than the surface treated glass cloth of Comparative Example 1, can obtain high insulation reliability in a printed wiring board, and are less likely to wrinkle when manufacturing prepreg. The surface treated glass cloths of Examples 1 to 6 have a surface treated layer on the surface, the surface treated layer containing a first silane coupling agent having at least one methacryloyl group and a second silane coupling agent represented by the general formula (1); Comparative Example 1 has a surface treated layer on the surface, the surface treated layer containing a first silane coupling agent having at least one methacryloyl group but not containing the second silane coupling agent represented by the general formula (1).

Claims

1. A surface treated glass cloth, characterized in that: The surface treated glass cloth has a surface treated layer on its surface. The surface treatment layer comprises a first silane coupling agent having at least one methacryloyl group and a second silane coupling agent represented by the following general formula (1): The ratio of the content of the second silane coupling agent to the content of the first silane coupling agent, that is, the content of the second silane coupling agent / the content of the first silane coupling agent, is in the range of 0.03 to 0.

17. The surface treatment layer does not contain a surfactant, The whitening distance degradation rate of the surface treated glass cloth is in the range of 3.8% to 14.7%. The whitening distance degradation rate is an increase rate of the whitening distance when the whitening distance of the surface-treated glass cloth whose surface-treated layer contains only the first silane coupling agent is used as a reference. The mass per unit area of ​​the surface treated glass cloth is 8 g / m 2 Above and 110g / m 2 the following, X(R) 3-n Yes n …(1), In the formula, X is an alkyl group having 1 to 4 carbon atoms, R is each independently a group selected from the group consisting of a methyl group, an ethyl group and a phenyl group, Y is each independently an alkoxy group having 1 to 6 carbon atoms, and n is an integer of 1 to 3.

2. The surface treated glass cloth according to claim 1, characterized in that: In the general formula (1) of the second silane coupling agent, X is a methyl group or an ethyl group.

3. The surface treated glass cloth according to claim 1, characterized in that: In the general formula (1) of the second silane coupling agent, X is a methyl group.

4. The surface treated glass cloth according to claim 1, characterized in that: The thickness of the surface treated glass cloth is in the range of 5 to 25 μm.

5. A prepreg, characterized in that: A surface-treated glass cloth comprising the surface-treated glass cloth according to any one of claims 1 to 4.

6. A printed wiring board, characterized in that A surface-treated glass cloth comprising the surface-treated glass cloth according to any one of claims 1 to 4.